The Actual Challenges and Efficient Ways of Translating Metaphore, Metonemy, Synechdoche In Literary Works - Nilufar, Bafoyeva (Indonesian Journal Publisher, 2024)
Translating stylistic devices like metaphor, metonymy, and synecdoche in literary works indeed poses significant challenges. Each device carries layers of meaning that are often tied to cultural contexts and linguistic nuances. Here’s a detailed look at the challenges involved and some effective strategies for translation.